2022
DOI: 10.2196/34200
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of a Soft Robotic Glove for Activities of Daily Living In People With Impaired Hand Strength: Protocol for a Multicenter Clinical Trial (iHand)

Abstract: Background Decline of hand function, especially reduced hand strength, is a common problem that can be caused by many disorders and results in difficulties performing activities of daily living. A wearable soft robotic glove may be a solution, enabling use of the affected arm and hand repeatedly during functional daily activities and providing intensive and task-specific training simultaneously with assistance of hand function. Objective We aim to inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Most participants reported that they used the glove 0.3-6 h daily, and the average grip strength across subjects improved from the initial measurement (9.9 ± 2.9 kg) to week 6 (14.0 ± 3.0 kg) to week 12 (14.0 ± 3.2 kg). Recently, it was evaluated over six weeks in a study involving 63 participants (between 18 and 90 years old) with impaired hand functions [71]. The protocol consisted of five assessments for each participant: three preassessments over three weeks as baselines before the intervention, a post-assessment within one week of the intervention's conclusion, and a follow-up assessment four weeks later to gauge the retention of effects.…”
Section: Carbonhand ®mentioning
confidence: 99%
See 1 more Smart Citation
“…Most participants reported that they used the glove 0.3-6 h daily, and the average grip strength across subjects improved from the initial measurement (9.9 ± 2.9 kg) to week 6 (14.0 ± 3.0 kg) to week 12 (14.0 ± 3.2 kg). Recently, it was evaluated over six weeks in a study involving 63 participants (between 18 and 90 years old) with impaired hand functions [71]. The protocol consisted of five assessments for each participant: three preassessments over three weeks as baselines before the intervention, a post-assessment within one week of the intervention's conclusion, and a follow-up assessment four weeks later to gauge the retention of effects.…”
Section: Carbonhand ®mentioning
confidence: 99%
“…The collected data can be used to assess the wearer's risk of developing injuries. Several clinical trials were conducted on SEM technology over a period of months [54,55,70,71]. The first preliminary study on the effects of Ironhand in working tasks (automotive assembly) was published in [72].…”
Section: Ironhand ®mentioning
confidence: 99%
“…The soft-robotic glove (see also (18)) used in this study was the Carbonhand system (Bioservo Technologies AG; Kista, Sweden) a fully wearable, battery-powered device (700g in total), which supports a person's grip (Figure 1). The system consists of a control unit and a glove.…”
Section: Interventionmentioning
confidence: 99%
“…Other outcome measures collected during this study, such as Action Research Arm Test (ARAT), pain ratings, Motor Activity Log, EuroQol-5D and glove use time, etc. (see 18), are not part of this paper and will be analyzed and published after study completion. All tests were performed without using the glove to examine the therapeutic effect.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Some studies have shown peripheral improvement in ankle biomechanical parameters, e.g., ankle ROM, muscle strength and size, and spasticity [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Studies have also shown improved balance scores [ 8 , 18 , 19 , 20 , 21 , 22 ]. However, studies examining a kinematic therapeutic effect have reached conflicting conclusions [ 11 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%